Analysis of factors in gadget addiction behavior (phone snubbing) among vocational students - Fitrani Rika Asnaria; Syaifullah Syaifullah; Sri Wahyuni Tanshzil (Universitas Sebelas Maret, 2025)
This study aims to explore and identify the factors contributing to gadget addiction in the form of phubbing (phone snubbing) among students at SMK Negeri 8 Bandung. A qualitative approach with a phenomenological design was employed to capture the lived experiences of the subjects. Data were collected through source and technique triangulation involving nine purposively selected informants: three students, three parents, the vice principal for student affairs, a guidance counselor, and a Pancasila education teacher. The findings indicate that phubbing behavior is driven by both internal and external factors. Internal factors include high intensity of gadget use, habitual patterns, boredom coping strategies, and the need for emotional satisfaction or entertainment. External factors encompass peer influence, easy internet access, and insufficient supervision or regulation from parents and teachers. The study concludes that phubbing among students is a multifaceted behavior shaped by both personal and environmental dynamics, necessitating comprehensive intervention from schools and families.